First experimental evidence of the third conformer of glycolic acid: combined matrix isolation, FTIR and theoretical study - Reva, Igor D. (2004)
The FT-IR spectra of monomeric glycolic acid, GA, isolated in argon and xenon matrices (at 10 and 20 K) were studied, enabling identification of three different conformers of GA. The most stable SSC conformer involves a hydrogen bond between the carbonyl group and the hydrogen atom of the alcohol hydroxyl group. The minor GAC and AAT forms involve intramolecular hydrogen bonds between alcohol and carboxyl OH groups, with alcohol and carboxylic groups serving as proton donors, respectively. The GAC conformer, predicted by theoretical calculations (at the DFT/B3LYP and MP2 levels with the 6-31++G(d,p) and aug-cc-pVDZ basis sets) as the second most stable form, was now experimentally identified for the first time.